Continuing decline of a keystone tree species in the Kruger National Park, South Africa. (3rd October 2012) - Helm, Chantal V.; Witkowski, Ed T. F.
Abstract Sclerocarya birrea subsp. caffra (marula), a keystone large tree species in southern Africa and heavily utilized by people and herbivores, is declining at an unprecedented rate in the Kruger National Park (KNP), South Africa. Due to increasing concerns over large tree declines in the KNP, mirroring those in eastern Africa over the last 50 years, and local extinctions of marula populations in the north‐western KNP, adult trees in the southern KNP were monitored between 2001 and 2010. Annual mortality rates across all adult size classes ranged between 3.2 and 4.6%. Loss of adult marula trees in some areas over the last decade exceeded 25%. Rainfall had a strong influence on mortality rates temporally and spatially, but the distance to the nearest perennial river had little influence. Overall, marula populations continue to decline and further local extinctions are possible. Given the clearly unacceptable trends of decline, the next step is to utilize this information (i) to develop predictive models for the future dynamics of marula populations incorporating all drivers; (ii) to advocate active management of refugia within the park where marula populations are protected from elephant impacts; and in combination with (iii) continued monitoring.